2008
DOI: 10.3748/wjg.14.2080
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic band ligation and endoscopic hemoclip placement for patients with Mallory-Weiss syndrome and active bleeding

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
1
30
0
2
Order By: Relevance
“…Surgical therapy is reported to be required in only 4%-8% of patients with DL. [10][11][12] It has been shown that EBL and haemoclip are equally effective and safe for the treatment of active bleeding in MWTs 12 and DL. 4 Postpolypectomy haemorrhage occurs in 0.5%-2.2% of cases of endoscopic polypectomy and may be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical therapy is reported to be required in only 4%-8% of patients with DL. [10][11][12] It has been shown that EBL and haemoclip are equally effective and safe for the treatment of active bleeding in MWTs 12 and DL. 4 Postpolypectomy haemorrhage occurs in 0.5%-2.2% of cases of endoscopic polypectomy and may be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…19 A prospective, randomized study of 41 patients with actively bleeding Mallory-Weiss tears randomized to clips or band ligation showed that all patients had immediate hemostasis, and only 1 patient rebled in the clip group and 2 in the banding group. 60 A study of 35 patients with actively bleeding or oozing Mallory-Weiss tears were prospectively randomized to either clip application or epinephrine injection. 61 There was no difference in immediate hemostasis or rebleeding.…”
Section: Mallory-weiss Tearsmentioning
confidence: 99%
“…Du fait d'un taux de récidive hémorragique pouvant aller de 5,8 à 44 % selon les séries utilisant l'adrénaline [16][17][18], la mise en place d'hémoclips, l'électrocoagulation, et plus récemment la ligature élastique ont été utilisées avec succès dans les SMW avec saignement actif [18][19][20][21][22]. La comparaison du résultat de ces différentes techniques avec ceux de l'injection d'adrénaline, n'a pas permis de montrer un bénéfice significatif en terme d'hémostase primaire ou de récidive hémorragique [16,20,23].…”
Section: Traitement Endoscopique Différentes Techniquesunclassified